“The Awakening”: anthropological notes on “negacionismo” and conspiracy theories about Covid-19 - Soto Bermant, Laia (Revista de Antropología Social, 2023)
This article explores, from an ethnographic perspective, the emergence of conspiracy theories around the pandemic that ravaged the world in 2020. On the one hand, the article seeks to explain the appearance and spread of these alternative stories. On the other, it questions the labelling process that helped official institutions discredit any “dissonant” narrative. These two perspectives are not mutually excluding, but rather they are complementary in showing what is at stake in the circulation of conspiracy theories: a profound discontent with a reality that has become increasingly difficult to distinguish from fiction.